Multi-Enzyme Assembly on T4 Phage Scaffold - Liu, Jinny L.; Zabetakis, Daniel; Breger, Joyce C.; Anderson, George P.; Goldman, Ellen R. (Frontiers in Bioengineering and Biotechnology, 2020)
Over the past two decades various scaffolds have been synthesized and designed to organize enzyme cascades spatially for enhanced enzyme activity based on the concepts of substrate channeling and stability. The most bio-compatible synthetic scaffolds known for enzyme immobilization are protein and DNA nanostructures. Herein, we examined the utility of the T4 phage capsid to serve as a naturally occurring protein scaffold for the immobilization of a three-enzyme cascade: Amylase, Maltase, and Glucokinase. Covalent constructs between each of the enzymes and the outer capsid protein Hoc were prepared through SpyTag-SpyCatcher pairing and successfully assembled onto phage capsids in vitro with an estimated average of 90 copies per capsid. The capsid immobilized Maltase has a 14-fold higher initial rate relative to Maltase free in solution. Kinetic analysis also revealed that the immobilized three-enzyme cascade has an 18-fold higher converted number of NAD+ to NADH relative to the mixtures in solution. Our results demonstrate that the T4 phage capsid can act as a naturally occurring scaffold with substantial potential to enhance enzyme activity by spatially organizing enzymes on the capsid Hoc.